Determinants of the intention to use National Insurance Mobile Application in Badung District based on Technology Acceptance Model Framework - Indrayathi, Putu Ayu; Megayanti, Ni Luh Komang; Ulandari, Luh Putu Sinthya; Kolozsvari, Laszlo Robert (Universitas Udayana, 2022)
Background and purpose: National Insurance Mobile Application (JKN Mobile) developed by Health Insurance Institution (BPJS Kesehatan) to facilitate the administrative activities of the National Health Insurance (JKN) participants. However, in practice, it has yet to be widely used by JKN participants. This study aims to explore factors determine participants' intention to use the JKN Mobile application based on the Technology Acceptance Model (TAM) Framework. Methods: This cross-sectional study was conducted in April-May 2021. The minimum required sample size was 99. Inclusion criteria were people 18 years of age or older, residing in Badung District, Bali Province and at least having used the JKN Mobile once. Data were collected through a self-administered questionnaire. A multivariable analysis was then conducted to determine the factors of intention to use the JKN Mobile application. Results: The proportion of JKN participants interested in using the JKN Mobile was 50%. Perceived usefulness, ease of use, credibility, and amount of information were correlated with the intention to use the JKN Mobile. The linear regression analysis showed that perceived usefulness is significantly associated with the intention to use JKN Mobile (aOR=9.68; 95%CI: 3.33-28.14; p=0.001). Conclusion: Participants' acceptability to use JKN Mobile is associated with the benefits of using such an application. It is thus imperative for BPJS Kesehatan to simultaneously update the design and features to be readily accepted and used by the public, which will later affect interest in using the application.